Penanaman Nilai Peduli Lingkungan Kebersihan Sekolah dalam Membentuk Karakter Siswa di SDI Pancasila Ponokawan Krian Sidoarjo - Oktavianti, Intan Indiana; El-Yunusi, Muhammad Yusron Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to describe the concern for environmental cleanliness in schools in determining the character of students. The research method used is a case study with a qualitative approach. This study uses descriptive analysis. Data was obtained by means of interviews, and observations that provide a clear representation of the steps taken to teach students about the surrounding environment. The results of this research will make life healthier, air cooler, learning more comfortable, and classrooms cleaner and disease-free. To create a clean school environment, it is important to instill knowledge about the environment from an early age in order to deepen understanding of the importance of the environment for humans, develop citizens who respect the environment and environmental awareness. Students both in the lower and upper grades can go hand in hand to carry out this activity in the school environment, there is a factor of togetherness, and in student interviews and observations. Each student can see how important it is to maintain the environment to be considered. Students will be more sensitive to the social environment so, whether there is one or not, they will try their best to protect the surrounding environment.